Glyphosate - A Silent, Slow Killer? - Hira Saleem,; Awan, Abdul Rafeh (Journal of the Pakistan Medical Association, 2023)
Madam, Glyphosate, commercially known as Round Up, is one of the most widely used herbicides and pesticides worldwide. As a synthetic organophosphate compound, it comes in a crystalline, odourless and colourless form. Most of the human exposure to this compound occurs during the process of its manufacturing, formulation and transport. Further exposure may come from the inhaling toxic fumes of nitrogen gas and phosphorus oxides produced when this pesticide undergoes decomposition, when farmers and gardeners use it on their crops, and when individuals come in contact with products containing it as the active ingredient (1). As of right now, there is a multitude of studies that link glyphosate to several morbidities. When a combined 9229 cases of farmers from North America, the European Union and Australia were assessed, glyphosate was directly linked to an increase in the onset of follicular lymphoma (2). It was also associated with allergic and non-allergic wheezing among farm women in the Agricultural Health Study (2005-2010), which focused on farmers in Iowa and North Carolina (3). Additionally, when tested on mice, exposure to glyphosate was found to increase TNFa in the brain and plasma, and the levels of soluble Amyloid Beta in the brain, suggesting a detrimental role to general health. Furthermore, glyphosate was one of the 11 pesticides studied and then found to have a direct correlation with the increase in overall cancer cases in Brazil. (5) Taking into consideration the aforementioned facts, it is vital to regulate the exposure of individuals to glyphosate to reduce the rising rate of morbidities. More guidelines and policies should be formulated to protect the health of individuals involved in glyphosate manufacturing, due to their exposure risk high. Pesticide leching into water sources should also be prevented to ensure that the general population does not end up consume them indirectly.